Poverty Alleviation through Geographic Targeting: How Much Does Disaggregation Help? - Elbers, Chris (World Bank, Washington, D.C., 2013)
Using recently completed "poverty maps" for Cambodia, Ecuador, and Madagascar, the authors simulate the impact on poverty of transferring an exogenously given budget to geographically defined subgroups of the population according to their relative poverty status. They find large gains from targeting smaller administrative units, such as districts or villages. But these gains are still far from the poverty reduction that would be possible had the planners had access to information on household level income or consumption. The results suggest that a useful way forward might be to combine fine geographic targeting using a poverty map with within-community targeting mechanisms.